Clinical risk management in hospital workforce: A systematic literature review - Nadhia Apriana; W. Victo Anggara Wises; Detania Sukarja (Jurnal Pendidikan Teknologi Kejuruan, 2026)
Clinical risk management in hospitals is increasingly shaped by workforce conditions, as clinical risks emerge from everyday decisions, communication, workload, training, reporting behaviour, and organisational support. This systematic literature review synthesised evidence on workforce-related clinical risks, management strategies, and future research directions in hospital settings. Following PRISMA 2020, relevant English-language peer-reviewed journal articles published between 2021 and 2026 were identified through Scopus and screened using predefined eligibility criteria. Twenty-five studies were included and analysed using narrative thematic synthesis with MMAT-informed quality appraisal. The findings show that workforce-related clinical risks are mainly associated with weak reporting culture and psychological safety; communication and handover failures; workload and staffing pressure; fatigue; training and competency gaps; clinical process risks; teamwork problems; and limited leadership or organisational learning. The main strategies used to manage these risks include incident reporting and learning systems, non-punitive safety culture, workforce training, structured risk assessment, communication standardisation, leadership support, and feedback-based organisational learning. However, most evidence remains descriptive, cross-sectional, qualitative, retrospective, single-site, or quality-improvement focused, with limited measurement of direct patient safety outcomes. Clinical risk management should therefore be understood as a continuous workforce-dependent safety process that connects staff conditions, risk pathways, organisational strategies, and sustained patient and staff safety outcomes.